Maxs War : The Story of a Ritchie Boy - Hellmann, Libby Fischer (Chicago : Red Herrings Press, 2024)
"As the Nazis sweep across Europe, Jewish teen Max and his parents flee persecution in Germany for Holland, where Max finds true friends and a life-altering romance. But when Hitler invades in 1940, Max must escape to Chicago, leaving his parents and friends behind. When he learns of his parents deportation and murder, Max immediately enlists in the US Army. After basic training he is sent to Camp Ritchie, Maryland, where he is trained in interrogation and counterintelligence. Deployed to the OSS as well, Max carries out dangerous missions in occupied countries. He also interrogates scores of German POWs, especially after D-Day and the Battle of the Bulge, where, despite life-threatening conditions, he elicits critical information about German troop movements. Post-war, he works for the Americans in the German denazification program, bringing him back to his Bavarian childhood home of Regensburg. Though the city avoided large-scale destruction, the Jewish community has been decimated. Max roams familiar yet strange streets, replaying memories of lives lost to unspeakable tragedy. While there, however, he reunites with someone from his past, who, like him, sought refuge abroad. Can they rebuild their lives... together?" -- Back cover.
Keywords: United States. -- Office of Strategic Services; Fiction; World War, 1939-1945 -- Jews; Fiction; World War, 1939-1945 -- Military intelligence -- United States; Fiction; Camp Albert C. Ritchie (Md.); Fiction; Novels; Romans